Fabrication of Low-Density Foam Liners in Hohlraums for NIF Targets. (17th February 2018) - Bhandarkar, Suhas; Baumann, Ted; Alfonso, Noel; Thomas, Cliff; Baker, Kevin; Moore, Alastair; Larson, Cindy; Bennett, Don; Sain, John; Nikroo, Abbas
Abstract: Low-density foam liners are seen as a means to mitigate hohlraum wall motion that can interfere with the inner set of beams that are pointed toward the middle section of the hohlraum. These liners need to meet several requirements, most notably the material choice and the maximum allowable solid fraction and thickness, which necessitate development of new processing capabilities. Here, we discuss our strategy and work on fabrication of a tantalum oxide foam liner and its assembly into targets for the National Ignition Facility (NIF). In particular, we discuss our approach to finding solutions to the unique challenges that come up in working with such low-density materials so as to be able establish a viable platform for production of cryogenic targets for NIF with foam-lined hohlraums.